전립선 암에서 Bicalutamide 사용으로 생긴 간질성 폐질환 1예 - 김양균; 김이형; 이재진; 최천웅; 유지홍; 박명재; 강홍모; Kim, Yang-Kyun; Kim, Yee-Hyung; Lee, Jae-Jin; Choi, Cheon-Woong; Yoo, Jee-Hong; et al. (Tuberculosis and respiratory diseases, 2010)
Androgen deprivation therapy, which is the standard treatment for metastatic prostate cancer, includes nonsteroidal antiandrogenic drugs, such as flutamide, nilutamide and bicalutamide. Of them, bicalutamide rarely induces interstitial pneumonia. We report a case of bicalutamide-induced interstitial pneumonia. A 68-year old male diagnosed with prostate cancer and multiple bone metastases presented with dry cough and low grade fever for 3 days. He had taken bicalutamide (50 mg/day) for 13 months. High resolution computed tomography revealed ground glass opacity in his right upper lung. The laboratory studies showed no eosinophilia in the serum and bronchoalveolar lavage fluid. Despite the use of antimicrobial agents for 2 weeks, the extent of the lung lesions increased to the left upper and right lower lung. He had no environmental exposure, collagen vascular disease and microbiological causes. Under the suspicion of bicalutamide-induced interstitial pneumonia, bicalutamide was stopped and prednisolone (1 mg/kg/ day) was initiated. The symptoms and radiologic abnormalities were resolved with residual minimal fibrosis.